MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PUISI MELALUI PROBLEM BASED LEARNING DENGAN LKPD INTERAKTIF - Ngatimah; Sandha Soemantri; Sayyidati Marlinda Yunita (Universitas Muhammadiyah Surabaya, 2024)
Increase of Indonesian learning capability used Contextual Learning approximation method of fourth grade student in Babat Jerawat I. The purpose of this research is to know the increase of Indonesian learning capability used Contextual Learning approximation method of fourth grade student in SDN 35 Teriang Jangkang. The research method used descriptive method. The research type is classroom action research. The research subject is a teacher in Babat Jerawat I and 30 student’s of fourth grade in SDN Babat Jerawat I. In this research can know plan learning capacity score data, perform learning capacity score data, and learning product score data. Based on result average in this research is: score average of plan learning capacity is 2, 83 on first cycle and 3, 27 on second cycle. Score average of perform learning capacity is 2, 78 on first cycle and 3, 25 on second cycle. Increase student’s learning capability is 52, 14 on first cycle and 71, 07 on second.